An alternative chlorine-assisted optimization of CdS/Sb2Se3 solar cells: Towards understanding of chlorine incorporation mechanism - Gopi, Sajeesh Vadakkedath; Spalatu, Nicolae; Katerski, Atanas; Kuliček, Jaroslav; Razek, Bohuslav; Ukraintsev, Egor; Bařinková, Markéta Šlapal; Zoppi, Guillaume; Grzibovskis, Raitis; Vembris, Aivars; Ignatane, Liga; Krunks, Malle; et al. (Elsevier Ltd, 2024)
The current strategies in the development of Sb2Se3 thin film solar cells involve fabrication and optimization of superstrate and substrate device architectures, with the preferable choice for TiO2 and CdS heterojunction layers. For CdS-based superstrate cells, several studies reported the necessity to apply CdCl2 or other metal halide-based post-deposition treatment (PDT), highlighting improvement of CdS/Sb2Se3 device efficiency. However, the need, effect, and mechanism of such PDT are very often not described. Additionally, the fact that many groups have not succeeded in demonstrating its benefits suggests that this strategy is not straightforward, requiring a deeper understanding towards a more unified concept. The present study proposes an alternative approach to the challenging CdCl2 PDT of CdS in CdS/Sb2Se3 device, involving controllable Cl incorporation in CdS films by systematically varying the concentration of NH4Cl in the CBD precursor solution from 1 to 8 mM. Structural and electrical characterizations are correlated with advanced measurements of Scanning Kelvin Probe, surface photovoltage, and atomic force microscopy to understand the impact of Cl incorporation on the properties of CdS films and CdS/Sb2Se3 devices. The validity of Cl incorporation in the CdS lattice and interdiffusion processes at the CdS-Sb2Se3 interface is confirmed by secondary ion mass spectrometry analysis. It is demonstrated that incorporation of 1 mM of NH4Cl, as a Cl source in CBD CdS, can boost the PCE of CdS/Sb2Se3 by ∼20 %. With this approach, we offer new perspectives on the optimization methodology for Cl-based CdS/Sb2Se3 device processing and complementary understanding of the physiochemistry behind these processes. © 2024 The Authors --//-- This is an open-access article Sajeesh Vadakkedath Gopi, Nicolae Spalatu, Atanas Katerski, Jaroslav Kuliček, Bohuslav Razek, Egor Ukraintsev, Markéta Šlapal Bařinková, Guillaume Zoppi, Raitis Grzibovskis, Aivars Vembris, Liga Ignatane, Malle Krunks, Ilona Oja Acik, An alternative chlorine-assisted optimization of CdS/Sb2Se3 solar cells: Towards understanding of chlorine incorporation mechanism, Journal of Alloys and Compounds, Volume 1005, 2024, 176175, ISSN 0925-8388, https://doi.org/10.1016/j.jallcom.2024.176175 published under the CC BY licence.
This study was funded by the Estonian Research Council projects PRG627 “Antimony chalcogenide thin films for next-generation semi- transparent solar cells applicable in electricity producing windows”, PSG689 “Bismuth Chalcogenide Thin-Film Disruptive Green Solar Technology for Next Generation Photovoltaics”, the Estonian Ministry of Education and Research project (TK210; TK210U8) „Center of Excellence in Sustainable Green Hydrogen and Energy Technologies“, and the European Union’s Horizon 2020 programme under the ERA Chair project 5GSOLAR grant agreement No 952509. The article is based upon work from COST Action Research and International Networking on Emerging Inorganic Chalcogenides for Photovoltaics (RENEW-PV), CA21148, supported by COST (European Cooperation in Science and Technology). The authors also acknowledge the Engineering and Physical Sciences Research Council (UK) for funding through Reimagining Photovoltaics Manufacturing (EP/W010062/1). The Institute of Solid State Physics of the University of Latvia, as a center of excellence, has received funding from the European Union framework program Horizon 2020 H2020-WIDESPREAD-01-2026-2017-TeamingPhase2 within the framework of grant agreement No. 739508 of the CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; CdS chlorine assisted optimization; Sb2Se3 thin film solar cell; Secondary ion mass spectroscopy; Vapor transport deposition